PENGARUH KUALITAS INFORMASI TERHADAP INDEKS KEPUASAN MASYARAKAT DI PENGADILAN AGAMA DAERAH ISTIMEWA YOGYAKARTA DENGAN KINERJA PELAYANAN SEBAGAI VARIABEL INTERVENING - Ade Ayu Damayanti Astuti Wijaya (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
This study aimed to provide empirical findings about the effect of information quality on the community satisfaction index with service performance as an intervening variable. This study used a mixed methods research which is combining quantitative methods and qualitative methods to obtain comprehensive results. The research population was all people who filed a lawsuit / petition in the Religious Courts in the Special Region of Yogyakartagreather than 100 people. The sampling technique in this research used a purposive sampling method. The sample of this research is 100 people who filed a lawsuit / petition in the Religious Courts in the Special Region of Yogyakarta. Interview informants in this study were 1 employee each in the area of the Religious Courts in the Special Region of Yogyakarta. The analysis technique used is to use the Partial Least Square (PLS) data analysis tool. The results showed that the quality of information had a positive and significant effect on the community satisfaction index in the Religious Courts in the Special Region of Yogyakarta with service performance as intervening variable. Community satisfaction index can be influenced directly or indirectly. The direct effect is greater than the indirect effect. This means that the mediating variable of service performance has not synergized with the quality of information to increase the community satisfaction index in the Religious Courts in the Special Region of Yogyakarta.